Economic burden of multiple sclerosis on Kuwait health care system - Alowayesh, Maryam S. (PLoS One, 2019)
BACKGROUND: Multiple Sclerosis (MS) is a chronic neurological disease with heavy economic and social burdens resulting in significant disability. OBJECTIVE: This study aims to (1) measure the cost of health resources utilization by MS patients and (2) to examine the difference in utilization and its attributed costs amongst patients who may have a different course of MS and expanded disability status scale (EDSS) scores. METHODS: A cross-sectional study using Kuwait National MS registry was conducted to estimate the costs of utilization of resources from 2011 to 2015. RESULTS: Between the period 2011–2015, 1344 MS patients were included in the registry. The average annual cost per MS patient has increased from $10,271 in 2011 to $17,296 in 2015. Utilization of disease-modifying therapies (DMTs) was the main driver of costs reaching 89.9% in 2015. Throughout the five-year period, the occurrence of relapses decreased from 21.8% to 12.2% (p <0.0001). During this same period, ambulatory relapse treatment increased by 5.8% while hospitalizations decreased by 2.6%. Patients with a moderate EDSS score (3.5–6) had the highest average cost (p<0.0001) compared to mild and severe EDSS scores. CONCLUSIONS: Multiple sclerosis has been a significant economic burden on the Kuwait healthcare system. DMTs are the main driver of cost.